Elements of economic culture as informal institutions in the economic development of Germany - Olczyk, Grzegorz (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: The author is interested in the problem of the economic development of a state wherein economic capital is described as a set of elements creating economic culture and informal institutions. Aim: Identification of the operational conditions and manifestations of institutional economics in Germany may obtain an accurate picture and understanding of the functioning their counterparts in Poland. Article is also a proposal for the development of research in the field of institutional economics and economic culture. Results: Putting the thesis that the German economy belongs to the group of the strongest in the world, the study revealed a pattern of results where the institutions were proposed as part of institutional economics, which determine economic development.